2001
DOI: 10.1097/00003246-200107000-00004
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of a high-carbohydrate diet in catabolic illness

Abstract: In severely burned pediatric patients, enteral nutrition supplied predominantly as carbohydrate rather than fat improves the net balance of skeletal muscle protein across the leg. This is attributable to decreased protein breakdown, suggesting a protein-sparing effect of high-carbohydrate feedings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
60
0

Year Published

2002
2002
2020
2020

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 107 publications
(63 citation statements)
references
References 19 publications
0
60
0
Order By: Relevance
“…fat synthesis from glucose), a metabolically undesirable energy-consuming process. Paradoxically, this contrasts with the ability of high glucose regimens to spare protein losses in burned patients receiving hyper-caloric feeding [24]. Whilst fat is present in nutrition formulas primarily to provide essential fatty acids that cannot be synthesised in humans, there is also reasonable evidence that, during iso-caloric feeding, fatty acids and carbohydrates exert an equally protein-sparing effect [20].…”
Section: Fat and Glucosementioning
confidence: 99%
“…fat synthesis from glucose), a metabolically undesirable energy-consuming process. Paradoxically, this contrasts with the ability of high glucose regimens to spare protein losses in burned patients receiving hyper-caloric feeding [24]. Whilst fat is present in nutrition formulas primarily to provide essential fatty acids that cannot be synthesised in humans, there is also reasonable evidence that, during iso-caloric feeding, fatty acids and carbohydrates exert an equally protein-sparing effect [20].…”
Section: Fat and Glucosementioning
confidence: 99%
“…The nitrogen sparing effects of glucose and lipid have been addressed in several reports with conflicting results. Some studies have found glucose achieves better nitrogen retention than lipids [15][16][17] , but usually there is no benefit of one fuel source over the other [18][19][20] . A review of the literature by Iapichino et al [21] , attempted to consider the potential confounding factors, and then compare the effects of glucose alone with the glucose-fat mixed system upon protein metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…EN was initiated at 20 mL/h and then increased by 20 mL/h every 4 h as tolerated until the goal rate was reached. The Carlson and Milner equations were used to predict calorie expenditure [13,14]. The Milner equation was created for >30 days after injury, with the factor of number of days post burn added to the Carlson equation using linear regression [14].…”
Section: Methodsmentioning
confidence: 99%